The Effectiveness of Procalysis Mobile to Patient Safety Culture Improvement - Natasya Heryani; Nurhasanah, Nurhasanah; Restu Yunus; Windi Indah Saputri (Jurnal EduHealth, 2022)
This study aimed to determine the effectiveness of Procalysis Mobile to improve the patient safety culture of hospital nurses in Samarinda City. This quasi-experimental research used a pretest-posttest control group design. The samples were 34 nurses that were divided into two groups. Group A received a Procalysis Mobile intervention, and group B received an intervention with a book of root cause analysis. The data were analyzed with an independent t-test. This study found that the p-value was 0.000 which means a significant difference between before and after the Procalysis Mobile intervention and the root cause analysis book intervention. Another result study was the mean value of the Procalysis Mobile intervention was higher (74.0) than the book intervention (38.0). The conclusion of this study was Procalysis Mobile has significantly different than a book intervention to patient safety culture improvement for nurses in hospitals.